Bronchial epithelial cells produce CXCL1 in response to LPS and TNFα: A potential role in the pathogenesis of COPD. (9th August 2018) - Inui, Toshiya; Watanabe, Masato; Nakamoto, Keitaro; Sada, Mitsuru; Hirata, Aya; Nakamura, Masuo; Honda, Kojiro; Ogawa, Yukari; Takata, Saori; Yokoyama, Takuma; Saraya, Takeshi; Kurai, Daisuke; et al.
Abstract: Rationale: Neutrophilic airway inflammation plays a central role in chronic obstructive pulmonary disease (COPD). CXC chemokine ligand (CXCL)1 is a neutrophil chemokine involved in the pathogenesis of COPD. However, its clinical significance in COPD patients is poorly understood.Aim of the study: To assess the production of CXCL1 by bronchial epithelial cells in response to lipopolysaccharide (LPS) and tumor necrosis factor (TNF)α.Materials and Methods: We measured sputum CXCL1 and CXCL8 levels in patients with COPD, asthma, and asthma-COPD overlap (ACO), and compared them to those of patients with interstitial pneumonia (IP). Using primary human bronchial epithelial cells and BEAS-2B cells, CXCL1 protein release and mRNA expression were measured after LPS or TNFα stimulation. We evaluated signal transduction mechanisms for CXCL1 production using nuclear factor-κ B (NF-kB) and mitogen-activated protein kinase (MAPK) inhibitors, and examined the effects of anti-inflammatory agents on CXCL1 production in BEAS-2B cells.Results: Sputum CXCL1 levels in COPD and ACO patients were higher than in IP patients, whereas sputum CXCL8 levels were not. Sputum CXCL1 levels were not affected by inhaled corticosteroid usage, whereas sputum CXCL8 levels tended to be affected. LPS and TNFα stimulated CXCL1 production and mRNA expression in bronchial epithelial cells. NF-kB and MAPK p38 were involved in LPS-induced CXCL1 production. Therapeutic anti-inflammatory agents minimally attenuated CXCL1 production and considerably inhibited CXCL8 production in BEAS-2B cells.Conclusions: Sputum CXCL1 levels is a potentially better diagnostic marker for COPD than sputum CXCL8 levels, which is explained by that CXCL1 production in bronchial epithelial cells is less affected by therapeutic anti-inflammatory agents than CXCL8 production.